Cutting loose eaudiobook - Andersen, Susan (Sisterhood Diaries, 2016)
Jane thinks nothing can make her lose her cool. But the princess of propriety blows a gasket the night she meets the contractor restoring the Wolcott mansion. Devlin Kavanagh's rugged sex appeal may buckle her knees, but the man is out of control. Jane had to deal with theatrics growing up—she won't tolerate them in someone hired to work on the house she and her two best friends have inherited. Dev could renovate the mansion in his sleep. But ever since the prissy owner spotted him jet-lagged and hit hard by a couple of welcome-home drinks, she's been on his case. Yet there's something about her. Jane hides behind conservative clothes and a frosty manner, but her seductive blue eyes and leopard-print heels hint at a woman just dying to cut loose . . . Contains mature themes.